Fat metabolism during exercise: a review--part II: regulation of metabolism and the effects of training - Jeukendrup, A. E.; Saris, W. H.; Wagenmakers, A. J. (International Journal of Sports Medicine, 1998)
This part discusses the complex regulation of fat metabolism. Catecholamines as a stimulator of lipolysis and insulin as a suppressor play very important roles in the regulation of fat oxidation. The interaction of carbohydrate and fat metabolism has been extensively studied in the past decennia but the understanding of this multifactorial regulation is complex and still incompletely understood. In 1963, Randle et al. proposed the glucose-fatty acid cycle as a possible mechanism, and more recently, regulation through malonyl-CoA has been put forward as a possible way to explain shifts in carbohydrate and fat metabolism at rest and during exercise. The exercise intensity affects fat oxidation mainly by increasing lipolysis and fatty acid availability during exercise of low to moderate intensity. At high exercise intensities, both a reduction in fatty acid availability (decreased RaFa) and intramuscular factors reduce fat oxidation. These intramuscular factors are largely unknown. The increased mitochondrial density after training and increased oxidative enzymes may partly explain the increased fatty acid oxidation during exercise as observed after training. However, also supply of fatty acids to the mitochondria may be important. The available evidence suggests that the additional fatty acids oxidized after training are primarily derived from intramuscular triacylglycerols and not from adipose tissue derived fatty acids or circulating triacylglycerols.